Multi-objective optimal design of periodically stiffened panels for vibration control using data-driven optimization method. (November 2021) - He, Meng-Xin; Lyu, Xiaofei; Zhai, Yujia; Tang, Ye; Yang, Tianzhi; Ding, Qian
Highlights: The band gap properties of the periodically stiffened panels are investigated. A data-driven optimization method is applied to obtain the Pareto solutions for vibration control. The optimized structures have targeted band gaps for reducing the vibration in different frequency ranges. The band gaps of two 3D printed periodically stiffened panels are investigated experimentally. Abstract: Vibration reduction properties of the periodically stiffened panels are studied using the data-driven optimization method and are verified using the 3D printing techniques. The dynamic responses and band gaps of periodically stiffened panels are calculated using the finite element method and periodic boundary conditions. To further develop the potential in vibration mitigation, a data-driven method is used to study the multi-objective structural optimization problem for minimizing the weight and mean square velocity simultaneously. The layout, thickness, and height of the stiffeners are taken as design variables. Numerical results show that the data-driven method is efficient in the optimal design of stiffened panels, and the optimized panels have targeted band gaps for different engineering demands. Moreover, two 3D printed panels are fabricated to study band gap properties of periodically stiffened panels experimentally.